2019
DOI: 10.3389/fmicb.2019.01033
|View full text |Cite
|
Sign up to set email alerts
|

Local Probiotic Lactobacillus crispatus and Lactobacillus delbrueckii Exhibit Strong Antifungal Effects Against Vulvovaginal Candidiasis in a Rat Model

Abstract: A comprehensive knowledge of the vaginal ecosystem is critical for the development of successful approaches to the treatment of infections. The role of Lactobacilli in preventing vulvovaginal candidiasis (VVC) is controversial. In this study, we investigated the therapeutic effects and mechanism of Lactobacillus crispatus or delbrueckii on vaginitis caused by Candida albicans in a Sprague–Dawley rat model. A microbiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…The anti- Candida activity observed was partially attributed to the presence of bacteriocin, hydrogen peroxide, and lactic acid [ 162 ]. In addition, Li et al implicated that both L. crispatus and L. delbrueckii were able to inhibit 60 to 70% of C. albicans in VVC Sprague-Dawley rat model as compared to non-treated control [ 163 ].…”
Section: Potential Of Lactobacillus In Keeping Vagmentioning
confidence: 99%
“…The anti- Candida activity observed was partially attributed to the presence of bacteriocin, hydrogen peroxide, and lactic acid [ 162 ]. In addition, Li et al implicated that both L. crispatus and L. delbrueckii were able to inhibit 60 to 70% of C. albicans in VVC Sprague-Dawley rat model as compared to non-treated control [ 163 ].…”
Section: Potential Of Lactobacillus In Keeping Vagmentioning
confidence: 99%
“…Numerous studies have shown the considerable probiotic potential of L. crispatus, such as modulating the host's immune system [2], reducing allergic symptoms in mice [3], down-regulating the expression of cancer genes, and inhibiting the proliferation of MDA-MB-231 breast cancer cell lines [4]. In addition, as one of the most detected Lactobacillus species in the healthy female vagina [5], L. crispatus can inhibit vaginal pathogenic microorganisms, and maintain the health of the female reproductive system [6][7][8]. Moreover, clinical trials have shown the therapeutic effect of L. crispatus on female vaginitis and recurrent urinary tract infection [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…They are associated with infertility, ectopic pregnancy, and sexually transmitted diseases. Gardnerella and Mobiluncus are the most common causative pathogens of BV (5), whereas Candida albicans is the most common causative pathogen of VVC (6). AV is often associated with pathogens such as Streptococcus agalactiae, Staphylococcus aureus, Escherichia coli, and Enterococcus faecalis (7).…”
Section: Introductionmentioning
confidence: 99%